2009
DOI: 10.3390/rs2010151
|View full text |Cite
|
Sign up to set email alerts
|

Application of Remote-sensing Data and Decision-Tree Analysis to Mapping Salt-Affected Soils over Large Areas

Abstract: Expert assessments for crop and range productivity of very-large arid and semiarid areas worldwide are ever more in demand and these studies require greater sensitivity in delineating the different grades or levels of soil salinity. In conjunction with field study in arid southeastern Oregon, we assess the merit of adding decision-tree analysis (DTA) to a commonly used remote-sensing method. Randomly sampled surface soil horizons were analyzed for saturation percentage, field capacity, pH and electrical conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
79
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(85 citation statements)
references
References 21 publications
4
79
0
2
Order By: Relevance
“…DT provides a robust and flexible approach when examining the effects of each input feature to determine each split in the final tree and select the most important input variables that achieve the best classification results. Studies indicate that decision tree classification is superior over traditional image classifiers [21,[46][47][48][49].…”
Section: Decision Treementioning
confidence: 99%
“…DT provides a robust and flexible approach when examining the effects of each input feature to determine each split in the final tree and select the most important input variables that achieve the best classification results. Studies indicate that decision tree classification is superior over traditional image classifiers [21,[46][47][48][49].…”
Section: Decision Treementioning
confidence: 99%
“…These include Landsat Thematic Mapper (TM), Landsat Multispectral Scanner System (MSS), Landsat Enhanced Thematic Mapper Plus (ETM+), SPOT, Advanced Spaceborne Thermal Emission and Reflection Radiometer (Terra-ASTER), Linear imaging self-scanning sensor (LISS-III) and IKONOS [23,49,50]. For example, in the United States of America (USA), Elnaggar and Noller [51] used Landsat TM imagery integrated with decision-tree analysis (DTA) to map soil salinity in central Malheur County. They found that there was a significant relationship between EC values and reflectance in Landsat bands 1, 2, 3 and 4 as well as the Brightness (BI) and Wetness (WI) indices.…”
Section: Multispectral Satellite Sensors For Mapping and Monitoring Smentioning
confidence: 99%
“…These include Landsat Thematic Mapper (TM), Landsat Multispectral Scanner System (MSS), Landsat Enhanced Thematic Mapper Plus (ETM+), SPOT, and Advanced Spaceborne Thermal Emission and Reflection Radiometer (Terra-ASTER) (Dwivedi, 2001;Verma et al, 1994). Elnaggar and Noller (2009) index. Maximum likelihood supervised classification was used to classify the image into nonsaline soils (EC < 4 dS/m) and saline soils, with accuracy of 97% and 60% respectively, whereas DTA predicted five classes of soil salinity with an overall accuracy of approximately 99%.…”
Section: Introductionmentioning
confidence: 99%